The Influence of the Health Crisis on the Romanian Tourism Industry: Array - Turtureanu, Anca; Cretu, Carmen Mihaela; Chitu, Florentina (Acta Universitatis Danubius. Œconomica, 2021)
At the beginning of February in 2020, no one could have imagined what would happen in the coming months due to the SARS-CoV-2 pandemic and, in particular, that it would become a health emergency and soon a global economic emergency. An economic emergency that we will probably compare to the crisis of 29. In the initial phase, the phenomenon was almost everywhere underestimated. All economic sectors were affected. Tourism is certainly one of the sectors that has suffered the most dramatic impact, the main cause being the lack of mobility of people, an essential condition for protection against Covid-19. The negative economic situation manifested itself in all sectors, affecting companies and destinations. The IMF (International Monetary Fund) predicted in mid-April 2020 a loss of -9.1% for Italy, -7.0% for Germany, over 10% for Greece, -5.9% in the US, -8% for Spain, -7.2% for France, -7.1% for the European Union as a whole, -6.5% for the United Kingdom, warning, however, that the compression of this sector could be even greater depending on the evolution of the pandemic. Many companies that belong to or have a connection with the various tourism sectors, immediately experienced a major liquidity crisis due to the almost total lack of demand. While expecting a certain recovery in the second half of the year, it is estimated that the turnover of hotel companies will decrease between 60% and 70% in 2020; Similar percentages indicate airlines, cruises, MICE sector (Meetings, Incentives, Conferencing, Exhibitions). In Romania, the HORECA sector registered massive decreases, and the forecast still cannot fully appreciate the phenomenon.